Pseudopoda fissa sp. nov. — first record of the genus from Vietnam (Araneae: Sparassidae) - Jäger, Peter; Vedel, Vincent (Zootaxa, 2005)
Pseudopoda fissa sp. nov. is described from Vietnam (male holotype). The new species belongs to the schwendingeri-group, previously known exclusively from northern Thailand. It is the first time that a representative of the genus Pseudopoda is recorded from Vietnam.